The outburst of a 60 min AM CVn reveals peculiar colour evolution: implications for outbursts in long-period double white dwarfs. Issue 1 (5th May 2021) - Rivera Sandoval, L E; Maccarone, T J; Cavecchi, Y; Britt, C; Zurek, D
ABSTRACT: We report on multiwavelength observations during quiescence and of the first detected outburst of the ≈60 min orbital period AM CVn SDSS J113732+405458. Using X-ray and UV observations, we determined an upper limit duration of the event of about 1 yr. The amplitude of the outburst was remarkably small, of around 1 mag in r and 0.5 mag in g . We have also investigated the colour variations of SDSS J113732+405458 and other long-period AM CVns in outbursts and identified a track on the colour–magnitude diagram that is not compatible with the predictions of the disc instability model, suggesting that some outbursts in long-period AM CVns are caused by enhanced mass-transfer. To our knowledge, these are the first studies of the colour evolution in AM CVns. During quiescence we measured an X-ray luminosity for SDSS J113732+405458 of ≈3 × 10 29 erg s −1 in the 0.5–10 keV band. This indicates a very low accretion rate, in agreement with the disc instability model for long-period systems. However, such a model predicts stable discs at somewhat long periods. The discovery of this system outburst, along with similarities to the long-period system SDSS J080710+485259 with a comparably long, weak outburst, indicates that these enhanced mass-transfer events may be more common in long-period AM CVns. A larger sample would be needed to determine empirically at what period, if any, the disc instability stops functioning entirely. Finally, we identified an infrared excess in the quiescence spectrum attributable to the donor. This makes SDSS J113732+405458 the second AM CVn to have a directly detected donor.